Changes in activity levels, physical functioning, and fall risk during the COVID‐19 pandemic. Issue 1 (24th September 2021) - Hoffman, Geoffrey J.; Malani, Preeti N.; Solway, Erica; Kirch, Matthias; Singer, Dianne C.; Kullgren, Jeffrey T.
Abstract: Background: Physical function worsens with older age, particularly for sedentary and socially isolated individuals, and this often leads to injuries. Through reductions in physical activity, the COVID‐19 pandemic may have worsened physical function and led to higher fall‐related risks. Methods: A nationally representative online survey of 2006 U.S. adults aged 50–80 was conducted in January 2021 to assess changes in health behaviors (worsened physical activity and less daily time spent on feet), social isolation (lack of companionship and perceived isolation), physical function (mobility and physical conditioning), and falls (falls and fear of falling) since March 2020. Multivariable logistic regression was used to assess relationships among physical activity, social isolation, physical function, falls, and fear of falling. Results: Among respondents, 740 (36.9%) reported reduced physical activity levels, 704 (35.1%) reported reduced daily time spent on their feet since March 2020, 712 (37.1%) reported lack of companionship, and 914 (45.9%) social isolation. In multivariable models, decreased physical activity (adjusted risk ratio, ARR: 2.92, 95% CI: 2.38, 3.61), less time spent on one's feet (ARR: 1.95, 95% CI: 1.62, 2.34), and social isolation (ARR: 1.51, 95% CI: 1.30, 1.74) were associated with greater risks of worsened physical conditioning. Decreased physical activity, time spent daily on one's feet, and social isolation were similarly associated with worsened mobility. Worsened mobility was associated with both greater risk of falling (ARR: 1.70, 95% CI: 1.35, 2.15) and worsened fear of falling (ARR: 2.02, 95% CI: 1.30, 3.13). Worsened physical conditioning and social isolation were also associated with greater risk of worsened fear of falling. Conclusion: The COVID‐19 pandemic was associated with worsened physical functioning and fall outcomes, with the greatest effect on individuals with reduced physical activity and social isolation. Public health actions to address reduced physical activity and social isolation among older adults are needed.